Measuring recovery-oriented rehabilitation language in clinical documentation to enhance recovery-oriented practice - Veronica De Monte; Angus Veitch; Frances Dark; Carla Meurk; Marianne Wyder; Maddison Wheeler; Kylie Carney; Stephen Parker; Steve Kisely; Dan Siskind (BJPsych Open, 2023)
Background Mental health services are encouraged to use language consistent with principles of recovery-oriented practice. This study presents a novel approach for identifying whether clinical documentation contains recovery-oriented rehabilitation language, and evaluates an intervention to improve the language used within a community-based rehabilitation team.